45. DEPRESSION STATUS AND ASSOCIATED FACTORS AMONG FINAL-YEAR HIGH SCHOOL STUDENTS IN HANOI (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the prevalence of depression and identify associated factors among final-year high school students in Hanoi.Subjects and methods: A cross-sectional descriptive study on 986 grade 12 high school students in Hanoi from December 1, 2023 to May 30, 2024.Results: A total of 51.9% of students exhibited depressive symptoms at varying severity levels: 29.9% had minimal symptoms, 10.7% mild, 6.4% moderate, and 4.9% severe. Factors that were statistically significantly associated with depression included: gender, academic pressure, emotional bullying,  cyberbullying, and smartphone addiction (p < 0.01). Among these, academic pressure, emotional bullying, cyberbullying, and smartphone addiction were associated with notably high odds ratios between affected and unaffected groups.Conclusion: A total of 51.9% of final-year high school students in Hanoi experienced depression at varying levels. Intervention strategies should focus on key associated factors, including academic pressure, emotional bullying, cyberbullying, and smartphone addiction among students.
Keywords: Depression; smartphone addiction; bullying; academic pressure; final-year high school students; 12th-grade students.